Why Milton Matters: A New Preface to His Writings - Wittreich, J. author. aut Link
XXV, 253 p. 16 illus.
Keywords: Wittreich demonstrates why Milton may prove to be the poet for the new millennium, in a book of interest to scholars and general readers. It engages the canonical Milton, as well as the Milton of popular culture, and uses the tools of theory- especially affective stylistics and reception history, to read Milton in his historical moment and our own.